PECULIARITIES OF THE FORECASTING OF DEMAND IN YOUNG PROFESSIONALS FOR THE NUCLEAR SECTOR - Nikolay I. Ishchenko; Galina G. Rekhina (Открытое образование (Москва), 2016)
The article observes such topics as specifics of the demand forecasting in the university graduates for the companies of the nuclear sector as well as the topic of the modern approach to such kind of HR problematic. We present the main steps of the demand forecasting process in the young professionals and the analytical results of the presented modeling.